1997
DOI: 10.1093/oxfordjournals.aje.a009172
|View full text |Cite
|
Sign up to set email alerts
|

Gender Gap in Cystic Fibrosis Mortality

Abstract: The authors conducted the largest study to date of survival in cystic fibrosis. The study cohort consisted of all patients with cystic fibrosis seen at Cystic Fibrosis Foundation-accredited care centers in the United States between 1988 and 1992 (n = 21,047), or approximately 85% of all US patients diagnosed with cystic fibrosis. Cox proportional hazards regression analysis was used to compare the age-specific mortality rates of males and females and to identify risk factors serving as potential explanatory va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
247
5
8

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(285 citation statements)
references
References 20 publications
25
247
5
8
Order By: Relevance
“…Females with CF have poorer lung function, higher mortality, earlier colonisation with Pseudomonas aeruginosa, and deteriorate with Burkholderia earlier than their male counterparts (Block et al, 2006, Corey et al, 1997, Rosenfeld et al, 1997, Demko et al, 1995, Jackson et al, 2011a, Jackson et al, 2011b. Recent work has focused on the role of steroid sex hormones such as estrogens in this "gender gap" (Chotirmall et al, 2010, Chotirmall et al, 2012a and has been reviewed elsewhere (Chotirmall et al, 2012b, Saint-Criq and Harvey, 2013, Sweezey and Ratjen, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Females with CF have poorer lung function, higher mortality, earlier colonisation with Pseudomonas aeruginosa, and deteriorate with Burkholderia earlier than their male counterparts (Block et al, 2006, Corey et al, 1997, Rosenfeld et al, 1997, Demko et al, 1995, Jackson et al, 2011a, Jackson et al, 2011b. Recent work has focused on the role of steroid sex hormones such as estrogens in this "gender gap" (Chotirmall et al, 2010, Chotirmall et al, 2012a and has been reviewed elsewhere (Chotirmall et al, 2012b, Saint-Criq and Harvey, 2013, Sweezey and Ratjen, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, for example, it occurs in 60-70 % of adults with CF (Stephenson, 2008). Both population-based and case-control studies have demonstrated that infection with P. aeruginosa appears to be an independent prognostic factor that carries with it an increased risk of death in CF patients, irrespective of lung function (Corey & Farewell, 1996;Rosenfeld et al, 1997).…”
Section: A Survey Of Clinically Relevant Quinolone Resistance Mutationsmentioning
confidence: 99%
“…It is important to understand this mechanism despite overall improved nutrition, growth and survival for CF, as gender disparity still exists with poorer long-term survival in the female population (Rosenfeld et al, 1997). The results from this study suggest that REE is elevated in females with CF before the commencement of puberty and remains elevated postpuberty.…”
Section: Discussionmentioning
confidence: 73%
“…Our previous larger cross-sectional study of both prepubertal and pubertal children with CF reported a greater elevation of REE in the females compared with males (Allen et al, 2003). This gender difference may explain why females with CF have inferior growth and overall impaired survival compared with males (Rosenfeld et al, 1997;Stallings, 2003). An even more recent small study in females suggested that the difference in REE between girls with CF and controls was greater in postmenarcheal than premenarcheal group (Stallings et al, 2005); however, in our preliminary study, we were unable to confirm this finding (Allen et al, 2004).…”
Section: Introductionmentioning
confidence: 88%